2019
DOI: 10.3389/fimmu.2018.03032
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G Regulation of the Evolutionary Race Between Adaptive Immunity and Viral Immune Escape Is Deeply Imprinted in the HIV Genome

Abstract: APOBEC3G (A3G) is a host enzyme that mutates the genomes of retroviruses like HIV. Since A3G is expressed pre-infection, it has classically been considered an agent of innate immunity. We and others previously showed that the impact of A3G-induced mutations on the HIV genome extends to adaptive immunity also, by generating cytotoxic T cell (CTL) escape mutations. Accordingly, HIV genomic sequences encoding CTL epitopes often contain A3G-mutable “hotspot” sequence motifs, presumably to channel A3G action toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 160 publications
(168 reference statements)
0
16
0
Order By: Relevance
“…Accumulating evidence indicates that A3G induces sub-lethal hypermutations in the Vif-positive HIV-1 genome and plays an important role in the production of defective proviral DNA in the HIV-1 reservoir (Borzooee et al, 2018; Cuevas et al, 2015; De Pasquale et al, 2013; Kieffer et al, 2005). A3G-induced hypermutations in vif and env genes of proviruses in vivo have been reported by several groups (Fourati et al, 2010; Simon et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence indicates that A3G induces sub-lethal hypermutations in the Vif-positive HIV-1 genome and plays an important role in the production of defective proviral DNA in the HIV-1 reservoir (Borzooee et al, 2018; Cuevas et al, 2015; De Pasquale et al, 2013; Kieffer et al, 2005). A3G-induced hypermutations in vif and env genes of proviruses in vivo have been reported by several groups (Fourati et al, 2010; Simon et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The development of A3G-mediated sub-lethal hypermutations in the Vif-positive HIV-1 genome in vitro and in vivo has been widely accepted (Borzooee et al, 2018; Cuevas et al, 2015; De Pasquale et al, 2013; Jern et al, 2009; Kieffer et al, 2005; Kim et al, 2010; Mulder et al, 2008; Sadler et al, 2010; Zhang et al, 2003). Given that USP49 protects A3G from the Vif-dependent and Vif-independent degradation pathway, it is important to study the possible correlation between USP49 expression and A3G expression, and subsequently HIV-1 disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that some A3 proteins may indirectly contribute to retroviral evolution, where the cytidine deaminase activity of the A3 protein helps the virus to acquire mutations that will make it more fit. Studies by Kim [3,5,10]. It was also shown that A3 proteins can mutate viruses so that they can use different receptors on the cell surface for entry into the host cell [5].…”
Section: Retroviral Evolutionmentioning
confidence: 99%
“…Immune escape refers to a situation where a pathogen evades detection by the host's immune system. In the case of retroviruses, this immune escape can be aided by A3 proteins [1,10,13]. As mentioned earlier, A3 proteins may sometimes cause sublethal mutations, which could help the virus to avoid detection by cytotoxic T cells (CTL), which kill infected cells [1,10,13].…”
Section: Immune Escapementioning
confidence: 99%